A refined tip correction based on decambering. Issue 5 (15th May 2015) - Sørensen, Jens N.; Dag, Kaya O.; Ramos‐García, Néstor
Abstract: A new tip correction for use in performance codes based on the blade element momentum (BEM) or the lifting‐line technique is presented. The correction modifies the circulation by taking into account the additional influence of the induction of the vortices in the wake, using the so‐called decambering effect and thin‐airfoil theory. A limitation of the standard Prandtl tip correction is that it represents the surface loading by a line distribution that does not take into account the actual shape of the rotor blade. Thus, the chord distribution does not appear as a parameter in the model, and the loading in the proximity of the tip is generally found to be overestimated. The new tip correction is implemented as an additional correction in order to represent the surface loading by a line distribution. Comparing computations using the new model with standard BEM results and computations using a 3D panel code show that the inclusion of the correction greatly improves the results. The new model also explains some of the discrepancies that earlier on have been observed when using a BEM technique based alone upon standard tip corrections. Copyright © 2015 John Wiley & Sons, Ltd.